The role of sirtuins in Alzheimer's disease - Lalla, Rakhee; Donmez, Gizem (Frontiers in Aging Neuroscience, 2013)
Sirtuins are highly conserved NAD+-dependent enzymes that were shown to have beneficial effects against age-related diseases. Alzheimer’s Disease (AD) is the most common neurodegenerative disorder associated with aging and the effects of sirtuins on AD have been investigated using different mouse and cell culture models. In most of these studies, it has been found that the overexpression of SIRT1 has protective effects against the AD phenotype. Therefore, designing therapeutics based on SIRT1 activity might be important to investigate treatment methods for this disease. In this review, we summarize the recent research regarding the roles of sirtuins and their potential roles in designing therapeutics for AD.